2012
DOI: 10.3389/fphys.2012.00257
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of TRPV1-Expressing Sensory Neurons Mediating Autonomic Dysreflexia Following Spinal Cord Injury

Abstract: Spinal cord injury (SCI) triggers profound changes in visceral and somatic targets of sensory neurons below the level of injury. Despite this, little is known about the influence of injury to the spinal cord on sensory ganglia. One of the defining characteristics of sensory neurons is the size of their cell body: for example, nociceptors are smaller in size than mechanoreceptors or proprioceptors. In these experiments, we first used a comprehensive immunohistochemical approach to characterize the size distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 89 publications
3
34
0
1
Order By: Relevance
“…22,23 It was shown that in the acute period post SCI, AD is typically less developed, and over time, as plastic changes within the spinal cord and aberrant inappropriate connections within the central and peripheral nervous system are established, AD becomes more prominent. 24 We also have to acknowledge a few limitations of this study. There are only 21 subjects included in this study and thus we are cognizant of the limitations of our analysis with respect to duration of effect of injury on the severity of AD.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 It was shown that in the acute period post SCI, AD is typically less developed, and over time, as plastic changes within the spinal cord and aberrant inappropriate connections within the central and peripheral nervous system are established, AD becomes more prominent. 24 We also have to acknowledge a few limitations of this study. There are only 21 subjects included in this study and thus we are cognizant of the limitations of our analysis with respect to duration of effect of injury on the severity of AD.…”
Section: Discussionmentioning
confidence: 99%
“…6,14,16 Also, it has been documented that AD induced by colorectal distention is mediated by C-fiber afferent pathways in SCI rats. 17 The present study further revealed that TRPV1 channel-expressing C-fiber bladder afferents are responsible for SCI-associated AD during bladder distention because the enhanced bladder-to-vascular reflex induced by bladder distention in SCI rats was significantly reduced by RTXinduced C-fiber desensitization. Although various mediators could contribute to afferent hyperexcitability after SCI, neurotrophic factors such as NGF released within the urinary bladder or the spinal cord reportedly have an important role in SCI-induced neuroplasticity.…”
Section: Autonomic Dysreflexia In Spinal Cord Injured Ratsmentioning
confidence: 68%
“…18 Recent data from animal studies suggest that TRPV1 (transient receptor potential vanilloid 1)-mediated stimuli from the colorectum are involved in conveying the stimuli that trigger episodes of AD. 19 Axons of the sensory neurons from the thoracolumbar and lumbosacral dorsal root ganglia expressing TRPA1 (transient receptor potential ankyrin 1) are present in the pelvic nerves that reach the distal colon. 20 It is believed that TRPV1 neurons are involved in the regulation of colonic motor function, but usually not in nociception.…”
Section: Discussionmentioning
confidence: 99%